Quantitative analysis in archaeology - VanPool, Todd L. 1968-; Leonard, Robert D. (Wiley-Blackwell, 2011)
"Quantitative analysis in archaeology introduces the application of quantitative methods in archaeology. It outlines conceptual and statistical principles, illustrates their application, and provides problem sets for practice. Discusses both methodological frameworks and quantitative methods of archaeological analysis. Presents statistical material in a clear and straightforward manner ideal for students and professionals in the field. Includes illustrative problem sets and practice exercises in each chapter that reinforce practical application of quantitative analysis"--Provided by publisher.